Whispers beneath the soil: soybean-microbe communication pathways in the rhizosphere - Cheng, Sau-Shan; Contador, Carolina A.; Zhang, Feng; Ho, Yun-Lam; Lam, Hon-Ming (Frontiers in Plant Science, 2025)
The rhizosphere is a dynamic ecosystem that hosts diverse microbial communities, essential for nutrient cycling, and promoting plant health and resistance to environmental stresses and pathogens. Understanding the communication strategies between plant roots and these microbial communities is vital for sustainable agriculture, as these interactions can enhance crop resilience and productivity while reducing the need for chemical fertilizers. Extensive research has focused on how soybean plants shape the rhizosphere microbiota and the signaling processes that promote these interactions; however, many influencing factors, particularly environmental stresses, remain unexplored. Key elements, including soybean genetics, growth development stages, soil properties, agricultural practices, and environmental conditions, all play crucial roles in shaping microbial symbioses. This review examines the intricate interactions between soybean and their rhizospheric microbiota, emphasizing how various stresses affect these relationships. It also discusses the role of secondary metabolites from both microbes and soybean in facilitating communication, alongside other factors that significantly influence these microbial interactions and soybean productivity.